2002
DOI: 10.1152/jn.00365.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pentobarbital Depressant Effects Are Independent of GABA Receptors in Auditory Thalamic Neurons

Abstract: Pentobarbital, a general anesthetic, has received extensive study for its ability to potentiate inhibition at GABAA subtype of receptors for GABA. Using whole cell current-clamp techniques and bath applications, we determined the effects of pentobarbital and GABA receptor antagonists on the membrane properties and tonic or burst firing of medial geniculate neurons in thalamic slices. Pentobarbital (0.01–200 μM) induced depressant effects in 50 of 66 neurons (76%). Pentobarbital hyperpolarized neurons by a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(43 reference statements)
0
11
0
1
Order By: Relevance
“…The second mechanism is GABA independent, namely the direct effect of PB on neuronal membrane potential. It has been reported that PB can cause hyperpolarization and therefore decrease the rate of action potential; this effect is not blocked by GABA antagonists [36]. Since the gap response threshold is determined by the recovery speed of neurons from the forward masking/inhibition effect of the pre-gap marker, the PB effect on gap response threshold must be considered as a combination of its depressant effect on neuronal membrane properties and inhibition due to forward masking.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism is GABA independent, namely the direct effect of PB on neuronal membrane potential. It has been reported that PB can cause hyperpolarization and therefore decrease the rate of action potential; this effect is not blocked by GABA antagonists [36]. Since the gap response threshold is determined by the recovery speed of neurons from the forward masking/inhibition effect of the pre-gap marker, the PB effect on gap response threshold must be considered as a combination of its depressant effect on neuronal membrane properties and inhibition due to forward masking.…”
Section: Discussionmentioning
confidence: 99%
“…Some effects of barbital may be connected with blocking (or enhancing the inactivation) of potential-dependent Na + conductance. The last effect was quite prominent in the auditory thalamus (Wan and Puil, 2002). Slowly inactivated Na + channels have been demonstrated in several animal models (Barlett and Wang, 2004;Toib et al, 1998).…”
Section: Putative Role Of Anesthetic and Gaba Inhibition In The Rate mentioning
confidence: 95%
“…In some cases, the depressing effects of pentobarbital did not involve known types of GABA receptor interactions (Wan and Puil, 2002). A prominent effect of some general anesthetics can be connected with an increase of potassium conductance (Ries and Puil, 1999).…”
Section: Putative Role Of Anesthetic and Gaba Inhibition In The Rate mentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the massive inhibition due to anesthesia diminished the reactivity of the sensory network and consequently blocked the auditory CS transmission from reaching the amygdala. In fact, general anesthetics, including sodium pentobarbital, are known to inhibit auditory transmission by altering neuronal activities in the inferior colliculus (Kuwada et al 1989), the auditory thalamus (Wan and Puil 2002), and the auditory cortex (Gaese and Ostwald 2001). To circumvent this problem, we employed the brain-stimulation CS, utilizing the known direct connection between the MGm and the LA.…”
Section: Timed Activation Of the Mpfc Is Necessary For Extinctionmentioning
confidence: 99%